PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, FIRM SIZE, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS - Galuh Dewi Oktaviani; Zaretta, Bara (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
Financial distress is a situation felt by a company facing a financial downturn which is very detrimental to the company's development, so that it will trigger many losses. This research aims to understand what influences the probability of financial distress in a company. This research uses Profitability (ROA), Leverage (DER), Liquidity (CR), Firm Size (LnTA), and Sales Growth (SG) for financial distress. The sample used for observations was 28 industrial sector companies listed on the Indonesia Stock Exchange for the 2018 - 2022 period. The sample was determined using a purposive sampling technique. The analysis technique used is logistic regression analysis. The observation results show that the ROA, CR and Firm Size proxies have a significant negative influence on financial distress and DER has a significant positive influence on financial distress. Meanwhile, Sales Growth results show that it has no effect on financial distress in industrial sector companies